Peningkatan Hasil Belajar Siswa dalam Memahami Materi Zakat melalui Penerapan Model Market Place Activity - Salmi Yanti (Kampus Akademik Publiser, 2024)
In Islamic teachings, zakat is worship which is fard 'Ain for every Muslim who is able and has excess assets. How to issue zakat has different provisions, both Zakat Fitrah and Zakat Mal. The purpose of this study is to explain in understanding the material of zakat and its provisions through the application of the Market Place Activity (MPA) model. The subjects of the study were the sixth grade students of SDN 12 Tiumang, Dharmasraya Regency, totaling 20 people with different socio- economic backgrounds. The results of this study indicate a significant change, namely in the first cycle of students who completed as many as 10 people or 50.0% classically, the second cycle completed 13 people or 65.0% and in Cycle III 17 people completed or 85.0% completely. classical, and it was also shown that there was an increase in student activity, namely in cycle I and Cycle II only on many criteria and cycle III on many criteria. Based on the results of this study, the researchers concluded that the Market Place Activity (MPA) model can improve students' ability to understand the material about paying zakat.